2021
DOI: 10.3390/molecules26051337
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating the Adverse Effects of Tomato mosaic tobamovirus Infecting Tomato Plants in Egypt by Boosting Immunity in Tomato Plants Using Zinc Oxide Nanoparticles

Abstract: Tomato mosaic virus (ToMV) is one of the economically damageable Tobamovirus infecting the tomato in Egypt that has caused significant losses. It is therefore of great interest to trigger systemic resistance to ToMV. In this endeavor, we aimed to explore the capacity of ZnO-NPs (zinc oxide nanoparticles) to trigger tomato plant resistance against ToMV. Effects of ZnO-NPs on tomato (Solanum lycopersicum L.) growth indices and antioxidant defense system activity under ToMV stress were investigated. Noticeably th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 75 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…Moisture loss or uptake is one of the most important factors that control the shelf life of foods. As water activity in a foodstuff decreases, the number and growth rate of microbial species able to grow in that environment also decreases [35][36]. These results are in accordance with the findings of Ibrahim [11] who recorded a significant decrease in moisture lost per hour due to an increase in temperature.…”
Section: Moisture Content Lost (% H -1 )supporting
confidence: 83%
“…Moisture loss or uptake is one of the most important factors that control the shelf life of foods. As water activity in a foodstuff decreases, the number and growth rate of microbial species able to grow in that environment also decreases [35][36]. These results are in accordance with the findings of Ibrahim [11] who recorded a significant decrease in moisture lost per hour due to an increase in temperature.…”
Section: Moisture Content Lost (% H -1 )supporting
confidence: 83%
“…Extensive reactive oxygen species (ROS) development under salinity stress is like other stressful circumstances. Considerable amounts of oxidative biomarkers like H2O2 were significantly increased under environmental stresses and used as a positive parameter to evaluate plants' tolerance to saline stress Sofy et al, 2021a). This study showed that all oxidative biomarkers were relatively low by inoculation of endophytic bacteria concerning the levels reported in salt-stressed plants.…”
mentioning
confidence: 70%
“…Other studies developed by ZnO Spherical nanoparticles by biosynthesis of ZnO-NPs via Catharanthus roseus were in the range of 23-57 nm, and we revealed excellent antibacterial activity against S. aureus, B. thuringiensis, and E. coli Green injury 70 . Not only for bacteria; Sofy et al reported that spraying Tomato plants with ZnO-NPs Tomv (100 mg / l ZnO-NPs) and to overcome the HVV infection by inducing antioxidant defence systems, it was reported that it is the desired strategy 71 . Other researchers have successfully prepared new salicylidene-iminothiazole and benzylidene-bis-iminothiazole bases to explore their antibacterial and antifungal performance 72 .…”
Section: Antimicrobial Property (Antibacterial and Antifungal Activity)mentioning
confidence: 99%